Measuring the Social Impact of Infrastructure Projects: The Case of Gdańsk International Fair Co. - Anna Zamojska; Joanna Próchniak (Journal of Entrepreneurship, Management and Innovation)

(untitled)
Efcient infrastructure is a prerequisite of, and critcal to, development. Only some projects generate a positve rate of return, but all of them should generate positve non-economic impacts and contribute social gains. Social impact is considered as a consequence or efect of decisions or interventons which lead to development. It can also be considered as a social consequence of development. The main problem of social costs and benefts is that the impact is difcult to predict and quantfy and can be taken into account diferently by authorites, decision makers and project developers. The main purpose of the paper is to identfy and demonstrate a concept of the social impact of infrastructure projects. The principal methods used are a review of existng social science literature and surveys based on focus group interviews, devoted stakeholders of infrastructure projects, and their involvement at diferent stages of the project. The expected result is a set of outputs and outcomes which demonstrates social impacts (costs and benefts) related to stakeholders’ groups of the analyzed project.